MANAJEMEN EMOSI DALAM PERSPEKTIF PSIKOLOGI ISLAM: STUDI PUSTAKA TERHADAP METODE PENCEGAHAN SIFAT GADAB (PEMARAH) DALAM INTERAKSI INTERPERSONAL - Muhammad Jembar Risky; Salwa Durrotun Nashah; Novia Karimahtunnisa; Salsabila Nadia Rahma Maulida; Mohammad Syaifuddin; Ahmad Ta’rifin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Emotional management is an important aspect of human life because uncontrolled emotions may trigger interpersonal conflict and psychological problems. In Islamic psychology, anger (gadab) is viewed as a natural emotion that must be controlled through spiritual and moral development. This study aims to analyze emotional management in the perspective of Islamic psychology and to identify methods for preventing excessive anger in interpersonal interactions. The research employed a qualitative approach using library research methods. Data were collected from the Qur’an, Hadith, books, and accredited scientific journals related to emotional regulation and Islamic psychology. The findings reveal that emotional management in Islam integrates spiritual, psychological, and moral dimensions through self-control, patience, dhikr, ablution, and interpersonal communication ethics. Emotional regulation contributes positively to psychological well-being, social harmony, and healthier interpersonal relationships. Furthermore, uncontrolled anger may lead to aggression, verbal conflict, and damaged social relationships, including in digital communication. Therefore, Islamic-based emotional management provides an effective approach to maintaining emotional stability and harmonious social interaction in modern life.